Peningkatan keterampilan bahasa pada anak usia dini melalui metode bercerita - Sriyono, Sriyono (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This paper aims to describe the application of improving language skills in early childhood through storytelling methods. The results of the discussion showed that the method of storytelling can improve language skills in early childhood, because storytelling is something that is exciting for children and has many benefits in developing children's abilities, especially in terms of language skills. This is because the storytelling method can improve the mastery of new vocabulary and encourage the activeness of children which in turn can improve children's language skills.